Ultrahigh‐performance liquid chromatography/electrospray ionization linear ion trap Orbitrap mass spectrometry of antioxidants (amines and phenols) applied in lubricant engineering†. (18th November 2013) - Kassler, Alexander; Pittenauer, Ernst; Doerr, Nicole; Allmaier, Guenter
<x xml:space="preserve">Abstract</x> RATIONALE For the qualification and quantification of antioxidants (aromatic amines and sterically hindered phenols), most of them applied as lubricant additives, two ultrahigh‐performance liquid chromatography (UHPLC) electrospray ionization mass spectrometric methods applying the positive and negative ion mode have been developed for lubricant design and engineering thus allowing e.g. the study of the degradation of lubricants. METHODS Based on the different chemical properties of the two groups of antioxidants, two methods offering a fast separation (10 min) without prior derivatization were developed. In order to reach these requirements, UHPLC was coupled with an LTQ Orbitrap hybrid tandem mass spectrometer with positive and negative ion electrospray ionization for simultaneous detection of spectra from UHPLC‐high‐resolution (HR)‐MS (full scan mode) and UHPLC‐low‐resolution linear ion trap MS2 (LITMS2), which we term UHPLC/HRMS‐LITMS2. RESULTS All 20 analytes investigated could be qualified by an UHPLC/HRMS‐LITMS2 approach consisting of simultaneous UHPLC/HRMS (elemental composition) and UHPLC/LITMS2 (diagnostic product ions) according to EC guidelines. Quantification was based on an UHPLC/LITMS2 approach due to increased sensitivity and selectivity compared to UHPLC/HRMS. Absolute quantification was only feasible for seven analytes with well‐specified purity of references whereas relative quantification was obtainable for another nine antioxidants. All of them showed good standard deviation and repeatability. CONCLUSIONS The combined methods allow qualitative and quantitative determination of a wide variety of different antioxidants including aminic/phenolic compounds applied in lubricant engineering. These data show that the developed methods will be versatile tools for further research on identification and characterization of the thermo‐oxidative degradation products of antioxidants in lubricants. Copyright © 2013 John Wiley & Sons, Ltd.